Dirofilaria repens Infection and Concomitant Meningoencephalitis - Poppert, Sven (Centers for Disease Control and Prevention, 2009)
Dirofilaria repens, a filarial nematode of dogs and other carnivores, can accidentally infect humans. Clinical symptoms are usually restricted to a subcutaneous nodule containing a single infertile parasite. Here, we report a case of D. repens infection with a subcutaneous gravid worm and the patient’s concomitant meningoencephalitis and aphasia.